Journalism in Pakistan: Practice and Function - Syed Abdul Sirajm Shahid Husssain (JSSH, 2023)
This study investigates how journalists in Pakistan perceive the importance of journalistic functions and how often do they practice them in their daily routine. The study analyzes a list of journalistic functions rated by the Pakistani Journalists for perceived importance and practice applying Principal Component Factor analysis, which generated eight constructs; i.e., News for Social Goods, Civic Journalism, Support of Government Policy, Culture and Development, Information and Country Image, Evaluating Government Development, Interpreting Government Policy, and Watchdog Function. The significant finding of the study is that Journalists in Pakistan often practice what they believe to be important.